2019
DOI: 10.1111/cch.12667
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity of mental comorbidity in children with new‐onset physical illness

Abstract: Background: Evidence suggests that physical and mental illnesses are strongly correlated in children. This study examined patterns of the chronicity of multimorbidity (co-occurring physical and mental illness); estimated homotypic continuity; and modelled factors associated with chronicity in children newly diagnosed with a chronic physical illness.Methods: Children aged 6-16 years diagnosed with one of asthma, diabetes, epilepsy, food allergy, or juvenile arthritis were recruited from two children's hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Youth with rheumatological conditions self-reported elevated symptoms of anxiety compared with their peers (d = 0.33). No significant differences in mental health were reported across the different types of rheumatological conditions, consistent with pre-pandemic studies that support non-categorical approaches (21,22) to understanding the intersection between physical and mental illness in children and youth (23)(24)(25)(26)(27). Notably however, studies have showed that clinical factors such as illness duration, severity, or exacerbations during the pandemic have no or minimal association with COVID-19-related mental health among youth with physical illness (16,20).…”
Section: Introductionsupporting
confidence: 70%
“…Youth with rheumatological conditions self-reported elevated symptoms of anxiety compared with their peers (d = 0.33). No significant differences in mental health were reported across the different types of rheumatological conditions, consistent with pre-pandemic studies that support non-categorical approaches (21,22) to understanding the intersection between physical and mental illness in children and youth (23)(24)(25)(26)(27). Notably however, studies have showed that clinical factors such as illness duration, severity, or exacerbations during the pandemic have no or minimal association with COVID-19-related mental health among youth with physical illness (16,20).…”
Section: Introductionsupporting
confidence: 70%
“…An estimated 15% of all children will experience the co-occurrence of at least one physical illness and at least one mental disorder—defined as physical-mental multimorbidity . 19 Physical-mental multimorbidity is often chronic and has been shown to be associated with significant negative impacts on daily functioning, 20 21 increases in mental health service use 22 and greater likelihood of suicidality 23 and risky substance use 24 25 among youth. However, despite increased interest in child mental health in recent decades as well as modern advancements in healthcare for children with physical illnesses, research on child physical-mental multimorbidity remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Rural-dwelling adolescents may have a greater burden of health risks compared to their urban counterparts, in part due to differences in health behaviors, economic disparities, and a lack of access to health-promoting services [ 4 , 5 ]. The onset of physical and mental health problems in adolescence can disrupt typical development and extend health risks into adulthood [ 6 ]. Establishing early, health-promoting behaviors is vital to mitigating health risks across the lifespan.…”
Section: Introductionmentioning
confidence: 99%